Determining growing-finishing pig lysine requirements and the effects of potassium bicarbonate and crystalline lysine level on finishing pig performance - Royall, Rafe Quinnlan (Kansas State University, 2022)
This thesis involves two studies to determine the effects of standardized ileal digestible (SID) lysine (Lys) requirements of growing-finishing pigs from 18 to 128 kg of body weight (BW) as well as evaluating the effects of adding potassium bicarbonate (KHCO₃) to diets with high or low crystalline lysine (L-Lys HCl) to influence dietary cation-anion difference (DCAD). Five experiments involving 2,903 pigs were conducted to determine the SID Lys requirement for maximum growth and economic return at five weight ranges throughout the growing and finishing phases. Using this data, we were able to create a pair of quadratic equations to estimate the SID Lys to Net Energy (NE) ratio required to achieve maximum growth potential and economic return throughout the growing-finishing phase. the quadratic equation of Lys:calorie ratio, g of SID Lys/Mcal of NE = 0.0002611 x BW², in kg – 0.0711037 x BW, in kg, + 7.284 was developed to reflect requirement for maximal growth performance from 18 to 128 kg BW. Optimal IOFC is best described by the quadratic equation: Lys:calorie ratio, g of SID Lys/Mcal of NE = 0.0001558 × BW², in kg, - 0.04030769 x BW + 5.410. Additionally, these results suggest that the most economical SID Lys level from 18 to 100 kg is below that for maximal growth rate. However, in 103 to 128 kg pigs, the SID Lys requirements for maximum growth performance and economic return are much more closely aligned. A second project utilized 1,944 pigs to determine if balancing DCAD levels, via added KHCO₃, in diets containing low or high levels of L-Lys HCl influences finishing pig growth performance or carcass characteristics. Dietary cation-anion difference is a measure of the level of monovalent ions (Na⁺, K⁺, and Cl⁻) within the diet, which correlates to the acid-base balance within the animal. Extreme DCAD levels, both high and low, have been shown to negatively impact feed intake and growth in pigs, previous research shows that a wide range may optimize performance.
Keywords: Amino acid; Dietary cation-anion difference; Growth; Grow-finish pig; Lysine; Potassium; Economics; Carcass; Crystalline lysine